Synchronous double cancers of the common bile duct - Sumiyoshi, Tatsuaki (Baishideng Publishing Group Co., Limited, 2012)
We report an extremely rare case of synchronous double cancers of the common bile duct without pancreaticobiliary maljunction. Only two similar cases have been reported in the English literature. Endoscopic re-trograde cholangiopancreatography showed a tuberous filling defect in the middle and superior parts of the common bile duct, and mild stenosis in the inferior duct. Computed tomography (CT) showed a well enhanced mass in the middle and superior parts of the common bile duct. A single cancer of the middle and superior bile duct was suspected and extra-hepatic bile duct resection was performed. CT eleven months after surgery revealed enhanced inferior bile duct wall and a slightly enhanced tumor within it. Retrospective review of the CT images taken before first surgery showed enhanced inferior bile duct wall without intrabiliary tumor only on the delayed phase. The inferior bile duct tumor was suspected to have originally co-existed with the middle and superior bile duct tumor. Pancreaticoduodenectomy was performed subsequently. Histopathological examination revealed that the middle and superior bile duct tumor was a moderately differentiated tubular adenocarcinoma while the inferior bile duct tumor was a papillary adenocarcinoma. The two tumors were separated and had different histological findings and growth patterns, further suggesting that they were two primary cancers.